microRNA-605 promotes cell proliferation, migration and invasion in non-small cell lung cancer by directly targeting LATS2 - Ye, Ying (Exp Ther Med, 2017)
Lung cancer is the most common cause of cancer- associated mortality for men and women worldwide. An increasing number of studies have reported that the abnormal expression of microRNAs contributes to the pathogenesis of the majority of human cancer types, including non-small cell lung cancer (NSCLC). The present study aimed to measure microRNA-650 (miR-650) expression in NSCLC and evaluate its function in NSCLC cells. Reverse transcription-quantitative polymerase chain reaction was used to determine miR-650 expression in NSCLC tissue samples and cell lines. Assays for cell proliferation, migration and invasion were performed to investigate the roles of miR-650 on NSCLC progression. Furthermore, the mechanisms underlying the effects of miR-650 on NSCLC cell growth and metastasis were determined. In the current study, miR-650 was demonstrated to be highly expressed in NSCLC tissue samples and cell lines. Inhibition of expression of miR-650 suppressed NSCLC cell proliferation, migration and invasion in vitro. Additionally, large tumor suppressor kinase 2 (LATS2) was identified as a direct target gene of miR-650 in NSCLC. LATS2 was revealed to be significantly downregulated in NSCLC tissues and was negatively correlated with miR-650 expression. Notably, LATS2 re-expression decreased NSCLC cell proliferation, migration and invasion; similar to the effects induced by miR-650 underexpression. In conclusion, the results of the current study suggest that miR-650 may serve as an oncogene by direct targeting LATS2 in NSCLC formation and progression.